Exterior view of Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Situated within the Bijolia temple complex, right next to the Mandakini Kund and behind the Mahakal Temple, stands the remarkable Undeshwar Temple. It is one of the mature examples of the Bhumija variety of temples. It has a central projection on each of the four faces, the quadrants so formed filled with miniature spires in vertical and horizontal rows right up to the top. The name Undeshwar originates from the fact that the inner sanctum of this temple is located about 2.4 meters below the floor level of the assembly hall.